Responses of Children to Art. Final Report - Child, Irvin L.; Iwao, Sumiko ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
This is the final report of a project designed to study developmental trends in young children's preferences in art. Individualized research procedures, adapted for use with pre-school age children, are described. Stimulus materials for the study include pairs of photographic prints of works of art, pairs of designs contrasting in regularity, and pairs of polygons differing in degree of complexity. These materials were chosen to represent distinct trends in development in school children's preferences as determined in an earlier study. The research findings are summarized. Comparison of the findings is made with data on a small sample of children from Japan. (SHM)
Sponsoring Agency: Office of Education (DHEW), Washington, DC. Bureau of Research.
Contract Number: OEG-1-70-0102(508).
Educational level discussed: Elementary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Aesthetic Education; Art Appreciation; Comparative Education; Educational Development; Educational Research; Elementary Education; Human Development; Preschool Children; Program Development; Projects; Trend Analysis